PEMBERIAN RANSUM DENGAN DOSIS HERBAL YANG BERBEDA TERHADAP SUSUT TETAS, MORTALITAS EMBRIO, DAN DAYA HIDUP DOC AYAM PERSILANGAN - Ramdan Febrianto, Rudy Sutrisna, Khaira Nova, dan Syahrio Tantalo (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This study aimed to determine the effect of giving ration with different herbal doses on the hatching shrinkage, embryo mortality, and DOC viability of crossbred chickens, and also to know the best dosage of herbal in the ration on the parameters. This research was conducted in October 2018 in the poultry house of Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The chickens used were 20 females and 4 males of crossbreed chickens between male Lohman brown and female kampong (3/4 Lohman brown + 1/4 kampong) in laying phase (aged 51 weeks). The treatment given were ration with different doses, namely without herbs (H0), 1 g/1 kg (H1), 2 g/1 kg (H2), and 3 g/1 kg (H3). Hatched shrinkage data were analyzed using variance analysis at 5% significance level and continued with the Least Significant Difference test. Data on embryo mortality and DOC viability obtained were tabulated and analyzed descriptively. The results showed that the lowest average value of hatching shrinkage was found in ration with herbal 1 g/kg, and the highest value of embryo mortality and the lowest DOC viability was found in ration treatment without herbs. Keywords: Rations, Hatching shrinkage, Embryo mortality, DOC viability, Crossbred chicken